Integrating English Language Learning and Social-Emotional Therapy for Autistic Children at Darul Fathonah: A Descriptive Case Study - Farida Farida; Ida Vera Sophya (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
Research on autism education has widely examined either language learning or social-emotional interventions; however, limited empirical attention has been given to how both can be integrated within the same learning routine, particularly in Indonesian therapy-education contexts. This study aimed to describe (1) the integration of English language learning and social-emotional therapy for autistic children, (2) the instructional and therapeutic strategies employed during implementation, and (3) observable changes in children’s English learning and social-emotional participation. A descriptive qualitative case study supported by descriptive quantitative indicators was conducted at Rumah Terapi ABK Darul Fathonah Kudus involving 11 autistic children aged 6–12 years. Data were collected through classroom observations, interviews with teachers, therapists, and parents, learning documentation, and pre- and post-session descriptive assessments. The integrated sessions employed picture-card activities, guided questioning, visual prompts, role-play, repetition, multisensory activities, and positive reinforcement. The findings indicate that English functioned not only as academic content but also as a medium for expressing preferences, emotions, and simple social responses. Descriptive indicators showed positive trends in vocabulary recognition, simple sentence production, question response, pronunciation, contextual understanding, and social-emotional participation after the sessions. This study contributes a contextual model of integrating language learning and social-emotional support within a naturalistic therapy-education setting and suggests that emotionally meaningful and visually supported English instruction may enhance participation among autistic children. The findings should be interpreted cautiously due to the bounded case-study design and are not intended as causal evidence.